An ovine tracheal explant culture model for allergic airway inflammation - Abeynaike Latasha; Meeusen Els NT; Bischof Robert J (BMC, 2010)
Abstract Background The airway epithelium is thought to play an important role in the pathogenesis of asthmatic disease. However, much of our understanding of airway epithelial cell function in asthma has been derived from in vitro studies that may not accurately reflect the interactive cellular and molecular pathways active between different tissue constituents in vivo. Methods Using a sheep model of allergic asthma, tracheal explants from normal sheep and allergic sheep exposed to house dust mite (HDM) allergen were established to investigate airway mucosal responses ex vivo. Explants were cultured for up to 48 h and tissues were stained to identify apoptotic cells, goblet cells, mast cells and eosinophils. The release of cytokines (IL-1α, IL-6 and TNF-α) by cultured tracheal explants, was assessed by ELISA. Results The general morphology and epithelial structure of the tracheal explants was well maintained in culture although evidence of advanced apoptosis within the mucosal layer was noted after culture for 48 h. The number of alcian blue/PAS positive mucus-secreting cells within the epithelial layer was reduced in all cultured explants compared with pre-cultured (0 h) explants, but the loss of staining was most evident in allergic tissues. Mast cell and eosinophil numbers were elevated in the allergic tracheal tissues compared to naïve controls, and in the allergic tissues there was a significant decline in mast cells after 24 h culture in the presence or absence of HDM allergen. IL-6 was released by allergic tracheal explants in culture but was undetected in cultured control explants. Conclusions Sheep tracheal explants maintain characteristics of the airway mucosa that may not be replicated when studying isolated cell populations in vitro. There were key differences identified in explants from allergic compared to control airways and in their responses in culture for 24 h. Importantly, this study establishes the potential for the application of tracheal explant cultures in relevant ex vivo investigations on the therapeutic and mechanistic modalities of asthmatic disease.